High Reproductive Success Despite Queuing – Socio-Sexual Development of Males in a Complex Social Environment - Mutwill, Alexandra M.; Zimmermann, Tobias D.; Reuland, Charel; Fuchs, Sebastian; Kunert, Joachim; Richter, S. Helene; Kaiser, Sylvia; Sachser, Norbert (Frontiers in Psychology, 2019)
The start of actual breeding in male social mammals can occur long after individuals attain sexual maturity. Mainly prevented from reproduction by older and dominant males, young males often queue until strong enough to compete for favorable social positions and, in this way, to obtain access to females. However, to what extent maturing males also apply tactics to reproduce before this time is largely unknown. Therefore, the aim of the present study was to elucidate male socio-sexual development from onset of sexual maturity through first mating success until the achievement of a stable social position in a complex social environment. For this purpose, guinea pigs were used as a model system and reproductive success of males living in large mixed-sex colonies was assessed during their first year of life. As a reference, males in a mixed-sex pair situation were examined. Pair-housed males reproduced for the first time around the onset of sexual maturity whereas colony-housed males did so much later in life and with a considerably higher variance. In colonies, reproductive success was significantly affected by dominance status. Dominance itself was age-dependent, with older males having significantly higher dominance ranks than younger males. Surprisingly, both younger and older colony-housed males attained substantial reproductive success of comparable amounts. Thus, younger males reproduced irrespective of queuing and already before reaching a high social status. This mating success of maturing males was most likely achieved via several reproductive tactics which were flexibly applied with the onset of sexual maturity. The period of socio-sexual development before a stable social position is established may, therefore, be a time during which male mammals use flexible behavioral tactics to achieve reproductive success more frequently than commonly is presumed. In addition, the findings strongly indicate that high behavioral plasticity exists well beyond sexual maturity.